Porphyromonas gingivalis Induced Fragmentation of Type IV Collagen Through Macrophage-Activated MMP-9: (In Vitro Study of Collagenolytic Mechanism in Pathogenesis of Atherosclerotic Plaque Rupture) - Siti Nurul Mubarokah; I Dewa Agung Susilawati; Sumarno Sumarno; I Ketut Gedhe Muliartha; Djanggan Sargowo (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Periodontitis is caused mostly by Porphyromonas gingivalis (P.gingivalis) and it is related to acute coronary syndrome. P.gingivalis readily invades blood circulation and potentially induces collagenolytic activity of inflammatory cells that results in collagen vascular degradation leading to atherosclerotic plague rupture (APR). APR is responsible for the occurence of fatal cardiovascular events such as acute myocardial infraction (AMI).AIMS: To show that P.gingivalis potentially induces fragmentation of the type IV vascular collagen due to macrophage-activated MMP-9.MATERIAL AND METHODS: The ability of P.gingivalis to induce the type IV collagen fragmentation, shown by digesting type IV collagen with the supernatant of monocyte-derived macrophage activated by exposure to P.gingivalis suspension for 18 hours, 37oC, 5%CO2. The type IV collagen fragments were analyzed by SDS-PAGE and confirmed by Western-blotting. Antibody of type IV collagen produced and confirmed by dot-blotting prior to its being used as primary antibody of Western-blotting. The existence of MMP-9 was detected by Dot-blot and Western-blot technique, while the MMP-9 activity was assessed by SDS-PAGE and zymograms.RESULTS: Our data showed that P.gingivalis induced macrophage to produce MMP-9 as one of collagenolytic components, and interaction with P.gingivalis proteases enhanced the proteolytic activity and resulted in degradation of type IV collagen with molecular weight of 88 kDa into two smaller fragments with molecular weight of 80 kDa and 60 kDa. CONCLUSION: P.gingivalis induced macrophage to activate its MMP-9 that led to fragmentation of vascular type IV collagen in the pathogenesis of atherosclerotic plaque rupture. KEYWORDS: P.gingivalis, macrophage, type IV collagen fragmentation, atherosclerotic plaque rupture, AMI